Diabetic myonecrosis: an uncommon diabetic complication. (3rd October 2019) - Kempegowda, Punith; Melson, Eka; Langman, Gerald; Khattar, Fady; Karamat, Muhammad; Altaf, Quratul-Ain
Abstract : Summary: Diabetic myonecrosis, also known as diabetic muscle infarction is a rare complication of diabetes mellitus usually associated with longstanding suboptimal glycaemic control. Although theories of atherosclerosis, diabetic microangiopathy, vasculitis, ischaemia-reperfusion injury and hypercoagulable state have been proposed to explain the pathophysiology, none of these have been able to individually explain the pathophysiology in entirety. Diabetic renal disease is the most common risk factor for developing DMN and its recurrence. The diagnosis is often missed due to lack of awareness and the presentation mimicking other conditions associated with DM. The routine laboratory investigations are often non-specific and do not provide much value in the diagnosis as well. Muscle biopsy can provide a definite diagnosis but is not currently recommended due to its invasiveness and association with prolonged time to symptoms resolution. Magnetic resonance imaging, in combination with classic history and risk factors can clinch the diagnosis. Treatment is generally analgesia and rest, although the former's use may be limited in the presence of renal disease. Learning points: Diabetic myonecrosis is a rare complication of diabetes mellitus associated with longstanding suboptimal glycaemic control. Diabetic renal disease is a known risk factor, although the evidence is merely observational. Although muscle biopsy could provide a definite diagnosis, it is not recommended as it can prolong the disease process and should be reserved only for cases not responding to conventional treatment. Typical MRI findings in combination with classic symptoms and risk factors can clinch the diagnosis Current treatment recommendations include NSAIDs and/or aspirin (if not contraindicated) alongside bed rest. Physiotherapy is not recommended in the acute phase but should be started as soon as patient is discharged from hospital. Optimal glycaemic control is key to prevent recurrence.